Efficient numerical computation of direct exchange areas in thermal radiation analysis. (2nd June 2016) - Feischl, M.; Führer, T.; Niederer, M.; Strommer, S.; Steinboeck, A.; Praetorius, D.
ABSTRACT: The analysis of thermal radiation in multisurface enclosures typically involves multiple integrals with four, five, or six variables. Major difficulties for the numerical evaluation of these integrals are nonconvex geometries and singular integral kernels. This paper presents hierarchical visibility concepts and coordinate transformations which eliminate these difficulties. In the transformed form, standard quadrature techniques are applied, and accurate results are achieved with moderate numerical effort. In benchmark example problems, the effectiveness and accuracy of the method are validated. A simulation model of an industrial furnace demonstrates the applicability of the method for large-scale problems.